1984
DOI: 10.1111/j.1095-8339.1984.tb01008.x
|View full text |Cite
|
Sign up to set email alerts
|

The identity of the oomycete causing ‘Kikuyu Yellows’, with a reclassification of the downy mildews

Abstract: Cultures of the causal fungus of Kikuyu Yellows disease of Pennisetum clandestinum isolated from Australia have been examined. The fungus is described. The oospore has three noteworthy features: it is plerotic even into the oogonial neck; the ooplast appears to develop a condensed core; the relative thicknesses of the oospore wall layers appear to differ from those of other Oomycetes. Oogonial characters and parasitism indicate an affinity with the graminicolous downy mildews. However, asexual sporulation is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
2

Year Published

1990
1990
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 9 publications
1
40
1
2
Order By: Relevance
“…1.4 THE NAME GAME -THE TAXONOMY OF ''CROWN'' OOMYCETES The current taxonomic organization of the oomycetes has largely been forged by two eminent scholars of zoosporic fungi, Frederick Sparrow (Sparrow, 1960, THE EVOLUTIONARY PHYLOGENY OF OOMYCETES 1976 and Michael Dick (Dick et al, 1984;Dick, 2001). In his encyclopedic treatise on aquatic fungi, Sparrow (1960) split the oomycetes into four orders, the Lagenidiales, Leptomitales, Peronosporales, and Saprolegniales.…”
Section: Kingdom Wars and Family Ties -A Case Of Conflicting Nomenclamentioning
confidence: 99%
See 1 more Smart Citation
“…1.4 THE NAME GAME -THE TAXONOMY OF ''CROWN'' OOMYCETES The current taxonomic organization of the oomycetes has largely been forged by two eminent scholars of zoosporic fungi, Frederick Sparrow (Sparrow, 1960, THE EVOLUTIONARY PHYLOGENY OF OOMYCETES 1976 and Michael Dick (Dick et al, 1984;Dick, 2001). In his encyclopedic treatise on aquatic fungi, Sparrow (1960) split the oomycetes into four orders, the Lagenidiales, Leptomitales, Peronosporales, and Saprolegniales.…”
Section: Kingdom Wars and Family Ties -A Case Of Conflicting Nomenclamentioning
confidence: 99%
“…Dick et al (1984) had placed Pachymetra together with Verrucalvus in their own family called the Verrucalvaceae, which were then included with the graminocolous downy mildews in the order Sclerosporales. As a result, Dick et al (1984) removed this group of well-known plant pathogens from the ''peronosporalean line'' to the Saprolegniales (Dick, 2001). However, recent molecular studies have shown that all the leaf-infecting genera of graminocolous downy mildews (e.g., Peronosclerospora, Sclerospora, etc.)…”
Section: A Place For the Water Molds -A Fishy Talementioning
confidence: 99%
“…Whereas long a direct phylogenetic line, Phytophthora-Plasmopara-Peronospora has been suggested, with several diverging minor lines of the other satellite genera, the hypothesis that Plasmopara and Peronospora rather have an independent origin from a basal Pythium/Phytophthora group has recently gained increasing support (Dick, 1988(Dick, , 1990; see also Fig. 36 in Dick et al, 1984). Although it is clear that DNA content alone cannot answer questions about phylo-genetic relationships, it may offer some arguments in the current debate.…”
Section: Infraspecific Variation In Genome Size and Host Specificitymentioning
confidence: 99%
“…mycelial agar disc taken from the mycelial margin of a Petri-dish culture in the linear phase of growth on CMA, except for Verrucalvus Javofaciens and Pachyrnetra chaunorhiza. In the case of these two species, it was necessary to use, as inoculum, a hemp seed which had been precolonized and incubated in glass distilled water (Dick et al, 1984. All pilot and Ryan tube cultures were incubated at 20 "C. Analysis of variance showed that any block-to-block differences had been removed by recording extension relative to the contemporaneous control.…”
Section: Saprolegniomycetidaementioning
confidence: 99%